Effect of extrusion cooking on β-glucan and fructan in wheat and rye bran - Bhat, Ramanath (2016)
In cereal industry, when cereal grains are milled to extract the starchy endosperm for white flour, large quantities of bran are classed as by-products and end up in animal feed. Bran, depending on the extraction rate, comprises of small amount of germ and endosperm along with aleurone layer, nucellar epidermis, seed coat and fruit coat. Bran is rich in dietary fibre, phytochemicals like phytic acid, phenolic components, lignans and flavonoids which is important in healthy human diet. To make use of all the nutrients present in this fraction of the cereal by-product could be a new value added product.